In spite of everything: Professionalism as mass customised bureaucratic production in a Danish government call centre. (1st July 2009) - ,; ,; ,
Abstract : This paper presents a study of the consequences of the transformation of part of the Danish Tax and Customs Administration (TAX) from a traditional white-collar public administration into a call centre. TAX participated in the study using ''Amica'' testing methods aimed at improving the psychosocial working environment in call centres. The results showed a surprising and rapid development from a situation where employees reported a stressful and unsatisfying work environment to one where the organisation had taken a giant stride towards improving the work environment, involving a major shift in leadership and employee identity. The paper discusses this change from a traditional white-collar model to a ''mass customised bureaucratic'' production one in a New Public Management setting that focuses on cost reduction, customer orientation, performance monitoring and documentation.